Application of Simple Additive Weighting Method in Student Decision Making in Choosing Study Programs - Ricko Gurning; Riska Ananda; Febri Sinabutar; Desi Damanik; Renny Karo Karo (SEAN Institute, 2024)
This study discusses the application of the Simple Additive Weighting (SAW) method in helping students of Santo Thomas Catholic University in choosing the right study program. Choosing the right study program is very important, because it can affect students' careers and future lives. Through the SAW method, this study identifies important criteria such as career prospects, personal interests, and academic achievements, each of which is weighted according to its level of importance. Each study program is evaluated and scored based on these criteria, and the results are summed up to obtain a final score. This study found that SAW is effective in providing objective and structured study program recommendations, but determining the right weighting is very important for the accuracy of the results. In addition, evaluating student satisfaction with the chosen study program also contributes to increasing the relevance of the recommendations given. Thus, the SAW method can be a useful tool to improve student satisfaction and learning outcomes in higher education.